Acne Vulgaris Management: A Review of First-Line and Advanced Pharmacological Treatments - Dobrzeniecki, Krzysztof; Zygmunt, Anna; Karoń, Karolina; Karoń, Łukasz; Karnas-Bogacka, Patrycja (Journal of Education, Health and Sport, 2025)
Introduction and objective: Acne vulgaris is a common chronic inflammatory skin disease affecting hair and sebaceous follicles, characterized by skin lesions most commonly appearing on the face. Several factors predispose individuals to the development of acne, including hormonal imbalances, genetic predisposition, and the use of certain medications. This review aims to evaluate and summarize first-line and advanced pharmacological treatments for acne vulgaris, highlighting their efficacy, safety, and emerging therapies for optimal management. Review methods: The literature review utilized databases covering sources from PubMed, Google Scholar, Scopus, and Web of Science using the search terms encompassing the following keywords: ‘acne vulgaris’ and ‘topical retinoid therapy’, ‘benzoyl peroxide’, ‘azelaic acid’, ‘topical antibiotics’, ‘oral antibiotics’, ‘contraceptive agents’, ‘antiandrogen therapy’, ‘isotretinoin’. Brief description of the state of knowledge: Current treatment methods range from topical therapies (i.e. antibiotics and retinoids) for mild cases to systemic medications (i.e. antibiotics, retinoids, and hormonal) for moderate to severe acne. In most cases, treatment should start with topical therapy. Summary: Early intervention is crucial to mitigate the risk of scarring and psychosocial consequences. Emerging therapeutic strategies have the potential to enhance treatment outcomes.